Serpinc1 Acts as a Tumor Suppressor in Hepatocellular Carcinoma Through Inducing Apoptosis and Blocking Macrophage Polarization in an Ubiquitin-Proteasome Manner - Xu, Dacai; Wu, Jiawen; Dong, Liang; Luo, Wenwen; Li, Lanying; Tang, Daolin; Liu, Jinbao (Frontiers in Oncology, 2021)
Serpinc1 is a serine protease inhibitor in the coagulation cascade, but its role in tumor biology remains obscure. Here, we report an unexpected role of serpinc1 in suppression of hepatocellular carcinoma (HCC). In HCC patients, the mRNA and protein expression of serpinc1 is up-regulated, which is negatively correlated with tumor grade, and has a better prognosis than patients with low serpinc1. In addition, patients with high expression of serpinc1 generally have a better tumor immune microenvironment, accompanied by changes in multiple immune cells and mediators. In particular, tumor-promoting M2 macrophages are negatively correlated with serpinc1 expression and the prognosis of HCC patients. In vitro experiments further show that overexpression of serpinc1 inhibits the growth of HCC cells (HepG2 and SMMC7721) by inducing apoptosis. Accordingly, cell co-culture experiments reveal the direct role of serpinc1-overexpressed HCC cells in inhibiting the formation of M2 macrophages. Subsequent unbiased quantitative proteomic and ubiquitinome analysis identify that multiple poly-ubiquitination of proteins involved in signal pathways (such as autophagy, apoptosis, lactate metabolism, and VEGF signaling) are regulated by serpinc1. Overall, these findings establish a serpinc1-dependent ubiquitin-proteasome system to control apoptosis and anti-tumor immunity.